Beyond Gendered Boundaries: The Implications of Riffat Hassan and Simone de Beauvoir’s Thought for Islamic Education in Indonesia - Mutmainah, Rofikasari; Maimun, Agus; Jamilah (UIN Sunan Gunung Djati Bandung, 2025)
This article discusses the philosophical studies of feminists (Simone de Beauvoir) and Islamic feminist theology (Riffat Hassan) and their impact on gender-responsive Islamic education in Indonesia. This study integrates secular and religious frameworks in the context of inclusive and emancipatory educational reform. Hassan's rereading of Islamic texts and canons highlights the patriarchal bias of the dominant interpretation and calls for a theology of gender justice and equal values for all people. On the other hand, de Beauvoir's existentialism, particularly the idea of women as the